Structural and chemical analysis of different types of raw cleaned (RC) Edible Bird’s Nest (EBN) - Bee, Hui Yeo; Rukayadi, Yaya; Oi, Ming Lai; Shew, Fung Wong; Chin, Ping Tan (Universiti Putra Malaysia, 2023)
Edible Bird's Nest (EBN) are known to have high nutritional values and medicinal properties. Raw cleaned (RC) EBN is EBN that has undergone cleaning processes. In this study, five types of RC EBN products were characterized by structural and chemical analyses. These are different grades of RC EBN products, including four products from house nest and one product from cave nest. RC EBN products from house nests were cup-shaped EBN (RCha), white EBN Biscuits (RChb), yellowish fragments (RChc) and rejected RC EBN (RChd), from cave nests were cup-shaped EBN (RCcave). The characterization includes physicochemical analysis (morphology, elemental composition, and color) and chemical analysis (nitrite concentration, antioxidant activity, total sialic acid content, total glycoprotein content and total polysaccharide content). Scanning electron microscope (SEM) images showed that no contaminants were found for all RC EBN products and that each RC EBN product has different structure. All RC EBN products have < 30 ppm nitrite and are export compliant. All RC EBNs showed antioxidant activity, DPPH and ABTS free radical scavenging activity, among which RCha and RChb had the highest (P < 0.05) antioxidant activity. RCcave shows the lowest (P < 0.05) total sialic acid, total glycoprotein and total polysaccharide content among RC EBN products.